Analysis Of OTUB1 Expression In Human Breast Adenocarcinoma Cell Line MCF7 And Human Breast Epithelial Cell Line MCF10A - Iskandar, Athirah (2019)
Post-translational modification (PTM) of protein is known to play a major role in protein function. One of the most important PTM is ubiquitination, in which the ubiquitin molecule(s) are added to a target protein by ubiquitin activating enzymes (E1s), ubiquitin conjugating enzymes (E2s) and ubiquitin ligases (E3s). This process is reversible by the action of specialized enzymes known as deubiquitinases (DUBs). OTUB1 is a DUBs that was reported to has critical roles in cancer initiation and progression. To investigate the role of OTUB1 in breast cancer, this preliminary study was conducted to compare the expression of OTUB1 in human breast adenocarcinoma cell line, MCF7 and human epithelial cell line, MCF10A. Expression of OTUB1 in MCF7 and MCF10A was analysed by quantitative real-time PCR and relative quantification (RQ) value was obtained using ΔΔCt method. Mann-Whitney test was used to evaluate the differences in OTUB1 expression levels between MCF7 and MCF10A. To support our qPCR study, computational analysis was also performed on selected microarray datasets from Gene Expression Omnibus (GEO) database (https://www.ncbi.nlm.nih.gov/geo/). qPCR analysis shows that OTUB1 expression was significantly higher in MCF7 compared to MCF10A (p = 0.037). Computational analysis on selected GEO microarray datasets shows that almost all probes corresponding to OTUB1 confirmed that OTUB1 expression is significantly higher in MCF7. Therefore, further studies should be done to uncover the role and function of OTUB1 in cancer-associated pathways.